A binary access control scheme with high data security. - Islam, Md. Rafiqul; Md. Sap, Mohd. Noor (Penerbit UTM Press, 2002)
An access control scheme for implementing the access matrix is presented. The proposed scheme is based upon binary form of access rights. In this scheme each user is assigned one key. The keys are possessed by the users and can be used to derive the access rights to the files. In this scheme attention has been given to the access information (keys of the users) itself This scheme is more effective and efficient for the systems where files are accessible to only limited number of users.